Effect of high pressure on structural modifications and enzymatic activity of a purified X-prolyl dipeptidyl aminopeptidase from Streptococcus thermophilus. (15th May 2018) - Giannoglou, M.; Alexandrakis, Z.; Stavros, Ph.; Katsaros, G.; Katapodis, P.; Nounesis, G.; Taoukis, P.
Highlights: The effect of high pressure and temperature on the activity of purified PepX was studied. PepX HP-induced conformational modifications were investigated. Activation or inactivation of purified PepX was observed depending on the applied HP-temperature conditions. PepX maintained its secondary structure, while the tertiary structure was substantially affected at 200 MPa, 20 °C, 20 min. HP processing at 450 MPa, 20 °C, 20 min, resulted in a final denaturated state of PepX. Abstract: PepX aminopeptidase from Streptococcus thermophilus ACA DC 0022, used in Greek Feta cheese manufacturing, was purified. PepX comprises two subunits of equal molecular mass estimated, using SDS-PAGE and native-PAGE electrophoresis, to be 86 kDa. The effects of high pressure processing (100–450 MPa, combined with 20–40 °C) on purified PepX activity and structure were studied. Activation of the enzyme was observed after processing at 100–200 MPa and 20–30 °C. More intense processing conditions led to enzyme inactivation. PepX HP-induced conformational changes were also investigated through application of Circular Dichroism spectroscopy (CD). Pressures up to 200 MPa resulted in a structurally molten globule-like state where PepX maintained its secondary structure but the tertiary structure was substantially affected and enzyme activity increased. Both secondary and tertiary structures were affected severely by higher pressures (450 MPa), which reduced enzyme activity.